Mental Health and the Covid19 Pandemic - Oliveira, Barbara Emanuele de Araujo (Universidade Estadual Paulista (Unesp), 2020)
In this episode of the Foreign Language Learner Podcast, a student in the second year of Letras Licenciatura at Unesp - São José do Rio Preto talks about living in the Covid19 pandemic.
Nível de proficiência de produção oral autoavaliado pelo aluno: B2
Keywords: COVID19 Pandemic; English language Pronunciation by foreigners; Mental health; Saúde mental; Pandemias; COVID-19; Língua inglesa Pronúncia estrangeira